Evaluation of management system, egg quality traits and farmers’ perception on exotic and indigenous chickens: The case of Buno Bedele zone, south west Ethiopia - Bekuma, Amanuel; Asefa, Meskerem; Tassew, Girma (Scientific Journal of Animal Science, 2020)
It is skeptical to plan and design chicken improvement strategy without considering chicken egg quality traits and farmers’ perception on exotic and indigenous chickens. In the present study, management system, egg quality traits and farmers’ perception on exotic and indigenous chickens were evaluated in selected districts of Buno Bedele zone, south west Ethiopia. A total of 180 randomly selected chicken owners were included in the study from nine purposively selected Peasant Associations (PAs) from the districts. And a total of 180 fresh eggs were purchased from sampled farmers on contractual bases for analyzing egg quality. SPSS software version 20 and SAS 1999 were used to analysis all the collected data. As the result of this study indicated farmers in the study areas were reared chicken with low management aspects. Based on the result, majority (73.9%) of the respondents favored to buy eggs of local chickens as they were considered to be tasty and the yellow colored yolk was commonly favored. The large egg size, brown-shelled eggs and yellow colour were the preferred egg quality traits by 48.3%, 52.8% and 81.7% of respondents, respectively. The mean external egg quality such as egg weight (g), egg length (mm), egg width (mm), shell thickness (mm) and shape index (%) of the local and exotic chicken were found to be 45.20±5.53 and 57.80±7.22, 49.6±3.8 and 54.8±1.7, 29.3±4.1and 41.0±1.5, 0.32±0.03 and 0.19±0.06 and 69.8 and 74.75, respectively. The other most important internal egg quality of (local and exotic) chickens considered in this study were yolk height (mm), albumen height (mm), albumen weight (g), Haugh unit (%) and yolk color; which were found to be (11.06 and 17.84), (2.87 and 6.92), (22.60 and 34.54), (52.5 and 71.25) and (10.33and 9.85), respectively. The eggs collected from the local chicken were found to have optimum shell thickness (0.32±0.03mm) and Haugh unit (52.5%). This might be attributed due to the high xanthophyll, which is responsible for deep yellow color of eggs; phosphorous and calcium contents of scavenging feed resources available in the study areas. In conclusion, egg quality of exotic chickens in the study areas performed impartially well, but it needs further comparative study.